The disenchanted - Schulberg, Budd (Fesler-Lampert Minnesota Heritage., 2012)
Considered by some to be Budd Schulberg's masterpiece, The Disenchanted tells the tragic story of Manley Halliday, a fabulously successful writer during the 1920s-a golden figure in a golden age-who by the late 1930s is forgotten by the literary establishment, living in Hollywood and writing for the film industry. Halliday is hired to work on a screenplay with a young writer in his twenties named Shep, who is desperate for success and idolizes Halliday. The two are sent to New York City, where a few drinks on the plane begin an epic disintegration on the part of Halliday due to.